CFD Simulation and Enhancement of Liquid-Liquid Mass Transfer under the Effect of 1.7 MHz Ultrasonic Waves - Mahdieh Abolhasani; Neda Azimi (Iranian Journal of Chemical Engineering)
This study investigates the two-phase flow simulation in a Y-type  micromixer with a circular pit at the junction with a 1.7 MHz ultrasonic (US) transducer. A CFD simulation is conducted on the micromixer under varying fluid flow rates. Initially, the simulation is performed without US waves, and subsequently, the US waves are applied. The influence of US waves on flow behavior, mass transfer coefficient (KLa), and extraction efficiency (E) is assessed and contrasts with the same in the scenario where no ultrasound is applied. The simulation outcomes exhibit strong agreement with the experimental findings of a reliable reference. The findings indicate that the flow pattern for both aqueous and organic phases is parallel within the micromixer when ultrasound is absent.   However, applying the US waves alters the flow pattern and enhances the mixing. Under the US field, the interface between the two phases is completely disrupted and the contact between them increases. It is concluded that applying US waves into the liquid medium enhances turbulence, mixing, and the mass transfer rate inside the micromixer.  The influence of the flow rate of the aqueous phase at different US powers on KLa and E was investigated. The decreasing trend of KLa is observed. The effect of the power of ultrasound (P=3.5, 5.25, and 7W) on KLa and E is investigated and results show that P= 7 W has the more ability to enhance the mass transfer rate. The maximum error that is obtained for KLa is 5.43 %, which shows the high accuracy of the CFD model.